2017
DOI: 10.1038/srep44489
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of twenty years of experimental warming on soil carbon, nitrogen, moisture and soil mites across alpine/subarctic tundra communities

Abstract: High-altitude and alpine areas are predicted to experience rapid and substantial increases in future temperature, which may have serious impacts on soil carbon, nutrient and soil fauna. Here we report the impact of 20 years of experimental warming on soil properties and soil mites in three contrasting plant communities in alpine/subarctic Sweden. Long-term warming decreased juvenile oribatid mite density, but had no effect on adult oribatids density, total mite density, any major mite group or the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…This ratio has been used to suggest nutrient availability in which fast-growing microbes like Proteobacteria are favored over slow-growing bacteria like Acidobacteria that are more successful in low nutrient environments [16,17]. The increasing soil temperature may act as a trigger and slowly induce changes or sequential reactions affecting the other environmental factors, such as pH, moisture, carbon, and nitrogen [51], which may explain the strong negative correlations between soil temperature with pH, and pH with moisture and nitrogen (Supplementary Fig 1). cas1 host composition, as a result, could be influenced by a combined effect of temperature, pH and moisture, and nutrients (total carbon, total nitrogen, nitrate, and ammonium) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio has been used to suggest nutrient availability in which fast-growing microbes like Proteobacteria are favored over slow-growing bacteria like Acidobacteria that are more successful in low nutrient environments [16,17]. The increasing soil temperature may act as a trigger and slowly induce changes or sequential reactions affecting the other environmental factors, such as pH, moisture, carbon, and nitrogen [51], which may explain the strong negative correlations between soil temperature with pH, and pH with moisture and nitrogen (Supplementary Fig 1). cas1 host composition, as a result, could be influenced by a combined effect of temperature, pH and moisture, and nutrients (total carbon, total nitrogen, nitrate, and ammonium) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alatalo et al [52] also reported that warming results in reduced TN content in soil. We found an increase in foliar N concentration under warming in the same experimental plots (data not shown).…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 94%
“…For example, Makkonen et al (2011) found drought-tolerant, large-bodied, surface-living Collembola to be most tolerant to experimental warming, and Bokhorst et al (2012) found small bodied fauna to be more sensitive to winter climate change than large-bodied species. For Acari, soft-bodied juvenile mites were found to be more susceptible to environmental changes than hard-bodied adults (Alatalo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For Acari, soft‐bodied juvenile mites were found to be more susceptible to environmental changes than hard‐bodied adults (Alatalo et al. ).…”
Section: Introductionmentioning
confidence: 99%